2016
DOI: 10.1289/ehp149
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Variability and Mortality: A Multi-Country Study

Abstract: Background:The evidence and method are limited for the associations between mortality and temperature variability (TV) within or between days.Objectives:We developed a novel method to calculate TV and investigated TV-mortality associations using a large multicountry data set.Methods:We collected daily data for temperature and mortality from 372 locations in 12 countries/regions (Australia, Brazil, Canada, China, Japan, Moldova, South Korea, Spain, Taiwan, Thailand, the United Kingdom, and the United States). W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
156
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 241 publications
(167 citation statements)
references
References 36 publications
9
156
0
2
Order By: Relevance
“…We used 4 df for both lag and temperature dimensions in the cross-basis term, since it has the lowest QAIC value from among the various simulated combinations of both lag and temperature with each ranging from 4 to 20 df (see Supplementary Materials Table S1), respectively, which are supported by previous studies [9,10,11,12]. Seven degrees of freedom per year was used for time trends [10,11,13,33], while 3 df was used for RHave ; both are in concurrence with previously published studies.…”
Section: Methodssupporting
confidence: 61%
“…We used 4 df for both lag and temperature dimensions in the cross-basis term, since it has the lowest QAIC value from among the various simulated combinations of both lag and temperature with each ranging from 4 to 20 df (see Supplementary Materials Table S1), respectively, which are supported by previous studies [9,10,11,12]. Seven degrees of freedom per year was used for time trends [10,11,13,33], while 3 df was used for RHave ; both are in concurrence with previously published studies.…”
Section: Methodssupporting
confidence: 61%
“…On the one hand, the winter excess mortality is changing over time but, on the other, indoor heating can relieve the threat of cold in a certain degree. A recent study suggests that, although unstable weather is a continuous process, impacts on health may be better captured by considering the temperature variability when assessing the associations between temperature and human health [36]. Only time will reveal exactly how climate change-related shifts in temperature distributions will affect mortality trends.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that sudden large changes in temperature can impair the human immune system and trigger immune evasion [24][25][26][27][28][29]. The possible mechanism is that the human thermoregulation of immune defense is less adjustable to the sudden large change in temperature [26,27] and less resistant to various diseases [24,25].…”
Section: Definition Of Rapid Weather Variabilitymentioning
confidence: 99%
“…It has been proposed that sudden large changes in temperature can impair the human immune system and trigger immune evasion [24][25][26][27][28][29]. The possible mechanism is that the human thermoregulation of immune defense is less adjustable to the sudden large change in temperature [26,27] and less resistant to various diseases [24,25]. Recently, studies showed that the sudden large change in temperature tends to cause high respiratory mortality [24][25][26][27]30] and to impact influenza seasonality [31].…”
Section: Definition Of Rapid Weather Variabilitymentioning
confidence: 99%
See 1 more Smart Citation